Leadership in the Church for a People of Hope. - Davies, Mervyn (Educationalist) (Continuum International Pub. Group, 2011)
This book explores Church leadership in the context of the 21 st century and to ask how it must change and adapt while being true to its roots; it bringd together insights from theology, history and the social sciences in a way that will show that it has much to learn from contemporary leadership studies while also being different in important ways. Many leadership studies either ignore the need for leadership to be properly ecclesiologically grounded and hence risk simply uncritically importing secular models, or put forward a simplistic biblical view of leadership which fails to make creativ.